Down to earth - Joshi, Sharad (New Delhi, 2010)
Examining the detrimental effects that (3z(Bgreen revolution(3y (Btechnology has had on India$1 (Bs agriculture$1 (Bincluding higher cultivation costs$1 (Bthis account provides the economic analysis and the political muscle to overcome agricultural issues. This compilation written by Sharad Joshi$1 (Bnational president of India$1 (Bs farmers' organization Shetkari Sanghatana$1 (Bargues that the government$1 (Bs agricultural policies made agriculture a losing proposition. Comprehensive and authoritative, these selected writings expound on the relatively more recent issues in agricultural development.s
Keywords: Agriculture-Economic aspects-India